Enhancing Learning Achievement Through Reward and Punishment: A Case Study of Grade VII Students at Frateran Santo Gabriel Catholic Middle School, Nunukan - Palungan, Yulius; Baharuddin, Baharuddin; Toding, Apriana (Siddiq Institute, 2024)
This study analyzes the impact of implementing the reward and punishment method in improving the learning achievement of grade VII students at SMP Katolik Frateran Santo Gabriel, Nunukan, North Kalimantan. Qualitative descriptive methods are used with data collection techniques through observation, interviews, and documentation.The results of the study indicate that the implementation of rewards, such as praise or gifts, motivates students to be more disciplined and active in learning. Conversely, punishment in the form of additional assignments or reprimands also plays a role in instilling responsibility. However, the effectiveness of this method is influenced by internal and external factors, such as student character, limited resources, and limited learning time. Some students have difficulty understanding the material due to low learning motivation and lack of active participation.Â This study confirms that the right combination of rewards and punishments can improve student achievement, but must be adjusted to the individual's character and the conditions of the learning environment. A more flexible approach is needed so that this method runs optimally and provides sustainable results in improving student motivation and academic achievementKeyword:Reward and punishment, academic achievement, motivation, discipline, Frateran Santo Gabriel Catholic Middle School